Strategies for Improving Education Accreditation in Junior High Schools: Challenges and Solutions - Nurhasanah, Nurhasanah; Amyus, Randi Saputra; Hamami, Abdul Rasyid; Sohiron, Sohiron (Journal of English Language and Education, 2025)
An education is recognized for its quality or quality of education after carrying out an accreditation process carried out by an independent institution. In today's world of education, there needs to be progress in order to keep up with the times, so that education remains relevant to the changes that occur in society. The challenges faced by education units are not easy because some things are not owned by education units. Everything in the education unit is the shared responsibility of all atake holders within the education unit. Of course, the challenges faced have solutions to solve of course by continuing to collaborate with every stake holder in the education unit. One of the challenges faced by secondary education units in improving accreditation in education units is the lack of human resources who have competencies in the field of education that have been certified by higher education institutions. The solution that can be given here is that every teacher is required to continue to improve themselves by participating in self-development and professional development activities to improve teacher professionalism. Then with the increase in teacher education, the accreditation of education units will increase. The Quality Imperative, being one of the key principles guiding organizational success to date, emphasizes the importance of prioritizing quality.